2009
DOI: 10.1007/s11250-009-9387-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences of thermophilic Campylobacter in cattle slaughtered at Morogoro municipal abattoir, Tanzania

Abstract: An investigation was conducted in Morogoro municipality to assess the likelihood of slaughter cattle posing public health risk of contaminating carcasses with thermophilic Campylobacter. Butchers and meat shopkeepers were interviewed on source of slaughter cattle, method of animal and carcass transportation, carcass dressing, meat storage facilities, access to clean water and availability of food hygiene practices. Faecal samples were collected from 107 slaughter cattle and after slaughter; four different part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
18
2
1
Order By: Relevance
“…of 9.5% on beef carcasses is in close agreement with a previous study that reported Campylobacter on 9.3% of dressed beef carcasses at the Morogoro municipal abattoir inTanzania. 61 In some countries, the prevalence of Campylobacter in beef carcasses was different and usually lower in comparison to this study. For example, the prevalence of Campylobacter in beef carcasses in Poland ranged between 2.7% and 14.9%, 19,91 while 3.5%, 3.3%, and 1.5% of the carcasses were contaminated in Finland, 38 Belgium, 33 and Canada, 11 respectively.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…of 9.5% on beef carcasses is in close agreement with a previous study that reported Campylobacter on 9.3% of dressed beef carcasses at the Morogoro municipal abattoir inTanzania. 61 In some countries, the prevalence of Campylobacter in beef carcasses was different and usually lower in comparison to this study. For example, the prevalence of Campylobacter in beef carcasses in Poland ranged between 2.7% and 14.9%, 19,91 while 3.5%, 3.3%, and 1.5% of the carcasses were contaminated in Finland, 38 Belgium, 33 and Canada, 11 respectively.…”
Section: Discussioncontrasting
confidence: 74%
“…38 While only one previous study addressed the prevalence of Campylobacter in slaughtered cattle in Morogoro, 61 here, we report the prevalence and antimicrobial resistance profiles of Campylobacter spp. recovered from raw milk and beef carcasses in three municipalities in Tanzania.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Spread of zoonotic diseases may be enhanced by poor hygiene and sanitation; malnutrition; poor health status; poor feeding habits; poor immunity and HIV and AIDS [3–8]. Thermophilic Campylobacter isolation rates of up to 70% have been reported in chickens [9], ducks 80% [10], beef 9.3% [11], pork 10.6% [12] and milk 13.4% (Kashoma, 2015; personal communication). Consumption of raw or undercooked meat, raw milk and untreated water are among predisposing factors to Campylobacter infection in humans [3, 13–16].…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, several Campylobacter prevalence studies have been performed in poultry, ruminants, and humans using Skirrow's protocol (Mdegela et al 2006;Chuma 2008;Nonga et al 2009;Kusiluka et al 2009). The prevalence of Campylobacter pathogens may be underreported because of the shortfalls which may be associated with the Skirrow's isolation method.…”
Section: Introductionmentioning
confidence: 99%